The dual aversion of Chile’s constitution-making process - Verdugo, Sergio; Prieto, Marcela (Oxford academic, 2021)
Chile initiated a constitution-making process in late 2019, after the major political parties signed an agreement to respond to the massive demonstrations that took over the streets in October of 2019. Dominant trends in Chile and Latin America’s constitutional thought typically examine this type of process through the lenses of the constituent power or transformative constitutionalism. The authors of this essay offer a different view. They argue that Chile’s constitution-making process, as designed by the multiparty agreement, manifests a double aversion: to avoid the Bolivarian way of constitution-making—including its associated constituent power narrative—and to put an end to the institutional and symbolic legacy of the Pinochet regime. In attempting to stay clear of these two negative models, the authors argue that the rules of the constitution-making process have adopted the main features of the post-sovereign model of constitution-making.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas